Enhancing MSME Competitiveness through Business Legality Mentoring and Digital Transformation in Probolinggo City - Aries Budi Wijayanto; Tjahjaningsih, Yustina Suhandini; Tri Prihatiningsih; Trismawati; Muhammad Alghifari; Fitri (Society : Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Laweyan Village, Probolinggo City, encounter intertwined challenges in business legality and digital readiness that hinder their competitiveness and access to formal markets. This community engagement program aimed to enhance MSME competitiveness through integrated mentoring on business legality covering Business Identification Number (NIB), and Home Industry Food Permit (PIRT), and digital transformation training. Using a participatory approach, the program involved 20 MSME participants from the food, crafts, and trade sectors in structured workshops, administrative facilitation, and digital mentoring. Results showed that 80% of participants successfully registered for NIB, and 50% initiated PIRT applications. Most participants also adopted QRIS-based digital payment systems, improved product branding, and created active social media profiles for online promotion. Evaluation through pre and post-tests revealed substantial increases in legal and digital literacy, along with improved transaction efficiency and customer engagement. These outcomes demonstrate that combining legality formalization with digital empowerment effectively enhances MSME competitiveness and resilience. Sustained collaboration among academic institutions, local government, and MSME actors is recommended to ensure long-term impact and scalability.